Non‐medical needs of older patients in the emergency department. (11th March 2016) - Liu, Bonnia; Taylor, David McD; Ling, Sophia L‐Y; MacGibbon, Paul
Abstract : Aim: To determine the non‐medical needs of older patients in the emergency department (ED). Methods: We undertook a cross‐sectional survey of three age groups (50–64, 65–79, 80 + years) using a self‐administered questionnaire with five response options (strongly agree–strongly disagree) for 31 items. Results: There were 548 patients enrolled. Significantly fewer older patients knew how to call for assistance ( P < 0.01), knew how the ED works ( P < 0.01), felt frightened by their illness ( P < 0.01) or felt that the ED lights were too bright ( P < 0.03). A substantial proportion of all patients did not agree that their illness and/or treatment had been well explained. Conclusion: Older patients appear resilient but need to be told to call for assistance when needed, to know how to call for this assistance and how the ED works. Clear information regarding their illness and treatment should be provided, particularly to younger patients who may be anxious.